2018
DOI: 10.1007/s00436-018-6055-8
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics of benzimidazole-resistant Haemonchus contortus and Haemonchus placei from buffalo and cattle: implications for the emergence and spread of resistance mutations

Abstract: The population genetics of nematode parasites are poorly understood with practical reference to the selection and spread of anthelmintic resistance mutations. Haemonchus species are important to study the nematode population genetics due to their clinical importance in ruminant livestock, and the availability of genomic resources. In the present study, it has been examined that Haemonchus contortus and Haemonchus placei populations from three buffalo and nine cattle hosts. Seventy-three individual adult worms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…In the present study, a low, but significant level of genetic differentiation has also been observed in the populations of H. placei (F st estimates maximum of 0.09) and H. contortus (F st estimates maximum of 0.02). Similar finding suggest that genetic differentiation does occur at low but significant level in H. contortus populations (Chaudhry et al, 2015a; Chaudhry et al, 2016b; Hunt et al, 2008; Redman et al, 2015) and a few reports in H. placei (Ali et al, 2018). The consequences of low levels of population genetic differentiation in part reflect high levels of animal movement (Hunt et al, 2008).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the present study, a low, but significant level of genetic differentiation has also been observed in the populations of H. placei (F st estimates maximum of 0.09) and H. contortus (F st estimates maximum of 0.02). Similar finding suggest that genetic differentiation does occur at low but significant level in H. contortus populations (Chaudhry et al, 2015a; Chaudhry et al, 2016b; Hunt et al, 2008; Redman et al, 2015) and a few reports in H. placei (Ali et al, 2018). The consequences of low levels of population genetic differentiation in part reflect high levels of animal movement (Hunt et al, 2008).…”
Section: Discussionsupporting
confidence: 83%
“…The data reported in the present study reveal a high genetic diversity among H. placei populations (allele richness 7.750 ± 0.603, expected heterozygosity 0.705) and H. contortus (allele richness 5.292 ± 0.47, expected heterozygosity 0.488). Similar studies have described a evidence of high genetic diversity in H. contortus populations (Chaudhry et al, 2015a; Chaudhry et al, 2016b; Hunt et al, 2008; Redman et al, 2015), but there are very few reports on H. placei (Ali et al, 2018). The impact of the high level of genetic diversity will not influence the benzimidazole resistance mutation rate under the impact of drug selection pressure, when compared both susceptible and resistant H. contortus and H. placei populations (Ali et al, 2018; Chaudhry et al, 2016a).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Adult Haemonchus worms were obtained from the abomasa of three buffalo and nine cattle, immediately following slaughter at six different abattoirs (Lahore, Faisalabad, Sargodha, Sahiwal, Okara and Gujranwala), where a high prevalence of Haemonchus was anticipated (Supplementary Table S1). It was described in our recent study (Ali et al, 2018). Adult worms were fixed in 80% ethanol immediately following removal from the host abomasa.…”
Section: Methodsmentioning
confidence: 89%
“…Genotyping of the single nucleotide polymorphism (SNP) at position 24 (P24) of the rDNA ITS-2 region was used to confirm the species identity of Haemonchus spp. in the cattle and buffalo parasite populations recently described by Ali et al (2018). The rDNA ITS-2 region was amplified from individual Haemonchus adult worm lysates using a “universal” forward primer complementary to 5.8S rDNA coding sequence and biotin labelled reverse primer complimentary to the 28S rDNA coding region (Chaudhry et al, 2015b).…”
Section: Methodsmentioning
confidence: 99%